MiRNA-26b Downregulation in Peripheral Blood Mononuclear Cells of Patients with Hepatitis C Associated Lymphomas is Restored by Successful Interferon-Free Antiviral Therapy. Issue 6 (August 2019) - Peveling-Oberhag, Jan; Bankov, Katrin; Dultz, Georg; Ballo, Olivier; Lohmeyer, Julian; Brunnberg, Uta; Marcu, Vasile; Walter, Dirk; Zeuzem, Stefan; Hansmann, Martin-Leo; Welzel, Tania M; Vermehren, Johannes
Background: Patients with chronic HCV infection are at increased risk of developing B-cell non-Hodgkin lymphoma (B-NHL). Regression of HCV-associated B-NHL (HCV-NHL) can be achieved through HCV eradication using interferon (IFN). However, only about two-thirds of patients with sustained virological response (SVR) also had a consecutive lymphoma response. miRNA-26b is associated with HCV-NHL response to antiviral therapy. Recent data suggest that IFN-free direct-acting antiviral (DAA) regimens also have anti-lymphoma activity in this patient population. Methods: We report four patients with HCV-NHL who were treated with different IFN-free DAA regimens as oncological monotherapy in our centre between 2015 and 2016. We analysed the virological and lymphoproliferative disease response. Moreover, we analysed miRNA-26b expression in peripheral blood mononuclear cells at different time points during antiviral therapy for all included patients as well as for a total of 10 controls with ( n =5) and without ( n =5) chronic HCV infection. Results: All patients had marginal zone lymphoma subtype and received different DAA regimens for 12–24 weeks. All four patients achieved SVR, but only three patients also had lymphoma response (one complete response, two partial responses). One patient showed progression to a high-grade lymphoma subtype after SVR. miRNA-26b expression was generally decreased in patients with HCV-NHL. Moreover, miRNA-26b expression was restored in those HCV-NHL patients with lymphoma response after 6 months ( P =0.009). Conclusions: We have demonstrated that IFN-free DAA treatment of HCV can improve or even cure NHL. miRNA-26b-levels could be a potentially useful biomarker to predict lymphoma response in HCV-NHL patients.